POLA PENDEKATAN DAKWAH BERKELANJUTAN: PERSPEKTIF MODAL SOSIAL - Abdul Najib (Prodi Pengembangan Masyarakat Islam Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2017)
Current model of dakwah has to deal with complexity of challenges. In tacking such complexity, relevant and contextual approaches are necessarily needed. One of them is social capital based approach. This approach highlights aspects of trust and honesty, norm and values, networking, solidarity, responsibility, local wisdom, local culture, harmony and quality of life. The use of this approach has already been able to answer the challenge of current Dakwah. From the perspective of social capital, the use of basic values from it contributes to the dai’s credibility building. This credibility results in sustainable activities of dakwah and therefore, creates more effective results. The effectiveness of sustainable dakwah emphasizes on efforts to set up good self-image for the da’i and improved relevant relational patterns with the mad’u.